2022
DOI: 10.3390/ijerph19020701
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Mobile DBT App and Its Impact on Suicidality in Transitional Age Youth with Borderline Personality Disorder: A Qualitative Study

Abstract: Contemporary performance and accessibility are features that enable mobile devices to be increasingly beneficial in the context of optimizing the treatment of psychiatric disorders. Smartphones have the potential to effectively support psychotherapeutic interventions among adolescents and young adults who require them. In the present study, the use and subjective influence of a smartphone app with content from dialectical behavior therapy (DBT) was investigated among transitional age youth (TAY) with borderlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…The majority of intervention studies ( k = 12 out of 16, 75.00%) used DBT techniques. Specifically, nine out of the 16 intervention studies (56.25%) were based on DBT (i.e., the interventions were DBT) [ 23 – 27 •, 30 , 32 , 34 , 35 ], and three (18.75%) were DBT-informed (i.e., included DBT elements) [ 29 , 31 , 37 •]. Only four intervention studies (25.00%) did not use DBT techniques [ 22 •, 28 , 33 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of intervention studies ( k = 12 out of 16, 75.00%) used DBT techniques. Specifically, nine out of the 16 intervention studies (56.25%) were based on DBT (i.e., the interventions were DBT) [ 23 – 27 •, 30 , 32 , 34 , 35 ], and three (18.75%) were DBT-informed (i.e., included DBT elements) [ 29 , 31 , 37 •]. Only four intervention studies (25.00%) did not use DBT techniques [ 22 •, 28 , 33 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the delivery format, most studies used smartphone apps to deliver the interventions. Twelve (63.16%) studies were smartphone app-based [ 17 ••, 23 , 24 , 27 •, 28 , 30 32 , 34 , 36 – 38 •], five (26.32%) were Internet-based [ 22 •, 25 , 29 , 33 , 35 ], one (5.26%) was email-based [ 26 ], and one review (5.26%) examined various forms of technology (e.g., virtual reality, mobile apps, computer-assisted) [ 18 ••]. The vast majority of the studies ( k = 18 out of 19, 94.74%) were conducted in North America and Europe, only one study [ 24 ] was conducted in Argentina.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mixed-method study, using in-depth interviews and questionnaires, revealed that such applications may make many of the therapeutic techniques in DBT treatment easier. Similarly, Schiffler et al designed a study that included 13 transitional age youth (18-23 year old patients) diagnosed with BPD and assessed their experiences and associated emotions before and after a testing period of 30 days while using a mobile DBT application [28]. However, they highlighted that this mobile application did not bring about any changes in the subjective view of suicidality.…”
Section: Mobile Applicationsmentioning
confidence: 99%